PENGARUH KOMUNIKASI PERSUASIF TERHADAP PARTISIPASI MASYARAKAT DALAM PENERAPAN KONSEP WISATA HALAL TOURISM DI PANTAI PULAU SANTEN BANYUWANGI - Karimah, Alifah (The Commercium, 2021)
Halal Tourism is a new tourism concept, so persuasive communication has an important role in implementing the concept to increase local community participation. Community participation will create community independence and reflect a form of sustainable development. But in fact the concept of halal tourism in Banyuwangi is no longer developing and ther is no form of independence in the community, so this study aims to find out how the influence of persuasive communication on communityparticipation in the application of the concept of halal tourism on the Pulau Santen Bayuwangi. This study uses quantitative research methods, with analysis of correlation coefficient of determination, and simple linier regression to measure the effect of variable X (persuasuive communication) on variable Y (public participation). The result of this study indicate that persuasive communication has a positive and significant influence on community participation, with coefficient value of 0,743 and a coefficient of determination value of 0,553 or 55,3% the influence of persuasive communication on public participation, and 44,7% influenced by other factors which were not researched. The form of community participation in Pulau Santen is reflected in the environmental field, which makes the tourist attraction cleaner and more well-maintained also increases public awareness and education regarding environmental hygiene. The form of persuasive communication of Banyuwangi local government can be directed at community human resources so that forms of innovation can come from the community, so that the community is no longer an object of development that only applies concepts from government but is also the subject of development and creates forms of sustainable development.